Islamic Economic Position as a Breakfast to Reducing Inflation - Nila Atikah; Akhmad Syafi'i; Upit Elya Rohimi; Prieska Rani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Inflation is a monetary event that results in a decrease in currency value for certain goods. These incidents cause disruption to the function of money, distort prices, destroy output, undermine efficiency and productive investment, and cause social injustice. The method in writing this article is to use a literature study with a descriptive-analytic qualitative approach, namely research that is emphasized tracking and analyzing. Written sources and related reading material to the theme were discussed for further study and in-depth study. This research was conducted to examine Inflation and how to overcome it in Islam. Inflation is a condition where there is an increase in prices in general, and it takes place continuously. Inflation is also a state of continuous decline in the currency's value. In general, Inflation is caused by: the sizeable public Demand for an item, an increase in production costs, and the very high circulation of money in society. Meanwhile, according to Al- Maqrizi Taqyudin, in the Islamic economy, Inflation is caused by natural Inflation ( naturally ) and human error inflation (by humans). According to its nature, Inflation is divided into a creeping, medium inflation (galloping Inflation), and high Inflation (hyper). Inflation). The cause of Inflation is divided into Requests pull Inflation and Cosh push Inflation. According to the origin, Inflation is divided into Inflation originating from within the country and abroad. Meanwhile, according to public expectations, it is divided into Expected Inflation and Unexpected Inflation. in conventional economies, the way to overcome Inflation is by implementing monetary policy, fiscal policy, non - monetary/non-fiscal policies. In Islam, Inflation is overcome by printing low/minimal amounts of money, executing the Dues Idle fund strategy, and implementing fiscal policy